2007
DOI: 10.1128/mcb.00565-07
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-Dependent Control of Bcl-x Alternative Splicing

Abstract: The alternative splicing of Bcl-x generates the proapoptotic Bcl-x S protein and the antiapoptotic isoform Bcl-x L . Bcl-x splicing is coupled to signal transduction, since ceramide, hormones, and growth factors alter the ratio of the Bcl-x isoforms in different cell lines. Here we report that the protein kinase C (PKC) inhibitor and apoptotic inducer staurosporine switches the production of Bcl-x towards the x S mRNA isoform in 293 cells. The increase in Bcl-x S elicited by staurosporine likely involves signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 95 publications
7
73
1
1
Order By: Relevance
“…It has been reported that a cis regulatory element, called SB1, is located in the first half of Bcl-x exon 2 (55). This 361-nucleotide-long region behaves as a splicing silencer, and its deletion stimulates the use of the Bcl-x S 5= splice site, thus promoting the expression of the Bcl-x S isoform in transfection assays performed with HEK293 and HeLa cells (55). We sought to determine whether TCERG1 affects Bcl-x alternative splicing through the SB1 element.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a cis regulatory element, called SB1, is located in the first half of Bcl-x exon 2 (55). This 361-nucleotide-long region behaves as a splicing silencer, and its deletion stimulates the use of the Bcl-x S 5= splice site, thus promoting the expression of the Bcl-x S isoform in transfection assays performed with HEK293 and HeLa cells (55). We sought to determine whether TCERG1 affects Bcl-x alternative splicing through the SB1 element.…”
Section: Resultsmentioning
confidence: 99%
“…The same blot was decorated with an anti-actin antibody (Sigma A2066) to correct for total protein content in different lanes. Anti-hnRNP A1 and A2 antibodies and anti-hnRNP F and H antibodies were described previously (49,50). Anti-hnRNP C1/C2 and G (C-17) were from Santa Cruz Biotechnologies, Inc. (sc-10037 and sc-4583, respectively); anti-hnRNP D/AUF1 was purchased from Upstate Biotechnology, Inc. (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…PKC␣/␤ has been previously linked to AS 4 regulation (11)(12)(13) and identified as one of the regulators of a group of AS events in HEK293T cells activated by epidermal growth factor (14). AS regulates eukaryotic gene expression by controlling the inclusion and exclusion of alternative exons within the coding and noncoding RNA transcripts (15,16).…”
mentioning
confidence: 99%